New Capabilities and Discovered Interconnectivities for a Curriculum-Integrated Multicourse Model Rocketry Project - Traum, Matthew J; Prantil, Vincent C.; Farrow, William C.; Weiss, Hope L. (Proceedings of the Wisconsin Space Conference, 2014)
To provide students a more coherent and cohesive view of the mechanical engineering curriculum, we created and are delivering a multicourse curriculum-integrated engineering project that permeates and unifies five required classes within our undergraduate curriculum: 1) Freshman Design, 2) Dynamics, 3) Numerical Analysis, 4) Fluid Mechanics, and 5) Thermodynamics. Students enrolled in these Rocket Project (RP) classes design, build, flight test, and analyze model rockets through hands-on exercises. These activities challenge students to work on different aspects of the same rocket project across all four years of their degree program. Critical to the seamless collection and presentation of data and experimental/numerical techniques across five courses was the development of new laboratory, field, and simulation capabilities driven by our goal: to measure all unknown variables needed for rocket performance analysis and modeling in-house without reliance on external data. These needed capabilities included: 1) collecting acceleration and barometric altitude data from a model rocket flight, 2) simulating via computer rocket trajectories for comparison to actual measured altitudes, 3) evaluating rocket performance by numerical methods to validate modeling assumptions, 4) determining rocket drag coefficient as a function of Reynolds number for velocities relevant to a launch, and 5) measuring rocket motor thrust as a function of time as well as the energy density of the fuel used. As these capabilities were developed, additional course interconnectivities and opportunities for data sharing were discovered and exploited to further enrich the course experience for students.Â 